(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Rectal cancer is the one the common cancer in Faridpur, Bangladesh. The clinical course of patient treated with surgery alone has been characterized by a high death rate and also by the pain and disability associate with pelvic recurrence of the tumor. Adjuvant chemotherapy combined with radiation has been studied for prevention of such reoccurrence. Most of the patients at our center are those who have already been in subjected to surgery in this hospital or other private hospital in this district or other district hospital. We studied role of Oxaliplatin and Capcitabine with Radiotherapy in AJCC stage IIB to IIIC locally advanced rectal cancer and toxicities in adjuvant settings. This study was done to assess the outcome of adjuvant chemoradiation in operated locally advanced treated cancer patients. A total of 30 patients were included in between June 2016 to June 2019 in non-randomized clinical trial. About 66.6% of the patient underwent low anterior resection and 33.3% had abdominoperineal resection. Patients were treated postoperatively with Oxaliplatin and capcitabine. Radiotherapy of 45 Gy in 20 fractions were delivered in concurrently with Capcitabine 825 mg/m2 from day 1 to day 5 of Radiotherapy at National Institute of Cancer Research and Hospital, Mohakhali, Dhaka, median follow-up was 3 years. At 3 years overall survival of operated patient was 66.3% with no disease relapse. Toxicities of this schedule were mostly Anemia and Gastrointestinal mucocitis but without treatment interruption. Combination of adjuvant chemotherapy and radiotherapy is effective modality in reducing local tumour recurrence and improves survival. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):101-105.